High Efficiency and Broadband Microstrip Leaky-Wave Antenna - Onofrio Losito (Active and Passive Electronic Components)
A novel layout of leaky-wave antennas based on tapered design has been proposed and investigated. The new tapered leaky-wave antenna (LWA) was designed running a simple procedure which uses an FDTD code, and using a suitable metal walls down the centerline along the length of the antenna connecting the conductor strip and the ground plane, which allows to use only half of the structure, the adoption of a simple feeding, and the reduction of sidelobes. The good performance of this new tapered microstrip LWA, with reference to conventional uniform microstrip LWAs, is mainly the wider band of 33% for VSWR <2, higher gain (12 dBi), and higher efficiency (up to 85%). Furthermore, from the theoretical analysis we can see that, decreasing the relative dielectric constant of the substrate, the bandwidth of the leaky-wave antenna becomes much wider, improving its performance.